A comparative study on the traditional versus modern yellow rice wine processing methods using Taohong Siwu Decoction for pharmaceutical production. (23rd May 2022) - Wang, Shengju; Jiang, Huajuan; Liu, Qianqian; Zhou, Yongfeng; Cheng, Yanfen; Zhou, Tao; Zhang, Jinming; He, Yao; Ren, Chaoxiang; Pei, Jin
Abstract: Ethnopharmacological relevance: Taohong Siwu Decoction (THSWD) is based on the "First Recipe of Gynecology." It is widely used in various blood stasis and deficiency syndromes, mainly in gynecological blood stasis, irregular menstruation, and dysmenorrhea. THSWD has great demand in traditional Chinese medicine (TCM), gynecology, orthopedics, and internal medicine. According to classical records, three medicinal materials, namely Rehmanniae radix, Angelica sinensis, and Carthamus tinctorius, used in THSWD need to be "washed with yellow rice wine." In the study of TCM prescriptions, the processing methods of medicinal materials not only needed to follow traditional records but also should consider modern technical conditions. Many medicinal materials in the repertoire of classical prescriptions involve yellow rice wine processing. Determining the processing method for medicinal materials is a key and difficult problem in the research and development of classical prescriptions. Aim of the study: With THSWD as the representative, this study analyzed differences between no processing method, the modern processing method of "stir-frying the materials with yellow rice wine, " and the traditional processing method of "washing with yellow rice wine." We focused on three aspects: composition, efficacy, and endogenous metabolism. This study aimed to provide a reference for research on the processing methods of medicinal materials used in classical prescriptions. Materials and methods: UPLC-Q-Orbitrap HRMS was used to quickly identify and classify the main chemical compounds of THSWD. A model of primary dysmenorrhea (PD) was established using estradiol benzoate combined with oxytocin. The latent period and writhing time; the levels of serum PGF2 α, PGE2, ET-1, and β -EP; and the pathological sections of the uterus were observed to determine their pharmacodynamic differences. GC-TOF/MS was used to analyze the differences in serum metabolites in rats. Results: A total of 54 active compounds were identified, and the results showed that catalpol and rehmapicroside disappeared following yellow rice wine processing. Compared with materials processed by the traditional method, the relative contents of 15 components, such as 5-hydroxymethylfurfural and digitalis C, increased in materials processed by the modern method. However, the relative contents of 16 components, such as hydroxysafflor yellow A, verbascoside, and ferulic acid, decreased in the modern processing method. The modern and classic processing methods acted on PD through different metabolic pathways. THSWD obtained by classical processing methods mainly treated PD through anti-inflammatory and estrogen metabolism pathways, whereas THSWD obtained by modern processing methods mainly treated PD through anti-inflammatory metabolic pathways. Conclusion: The study revealed the differences in different yellow rice wine processing methods in terms of chemical composition of the THSWD obtained, as well as the mechanisms of action for the treatment of PD. This study provides a reference for the clinical application of THSWD and development of classical prescription preparations. Graphical abstract: Image 1